CARDIOVASCULAR RISK AND NEUROTIC DISORDERS WITH PROTRACTED COURSE IN YOUNG PEOPLE - Панченко, М.С. (World of Medicine and Biology, 2014)
The aim of the research was to study the frequency and kind of different clinical variants of neurotic disorders with protracted course among patients, stratified by the level of cardiovascular risk. Materials and methods. The primary information base for the implementation of research was the result of complex clinical and anamnestic survey of 450 young patients, 400 of them had NPPS and who were previously stratified by the level of cardiovascular risk (CVR), defined by the «SCORE» method [1, 16]. 99 patients were assigned to the group of minimum (low) CVR (nLOW = 99), 102 patients - medium (nMED = 102), 97 patients - high CVR (nHIGH = 97) and 102 persons with diagnosed cardiovascular disease were assigned to a group with realized CVR (nX = 102). Results and their discussion. Clinical psychopathology research let us to determine the structure of NDPC and general patterns of distribution of its clinical variants depending on the level of CVR. However, certain differences were found, ie, each group had its quantitative and qualitative features of NDPC clinical patterns. Thus, it was found, that among the 99 patients with a minimum CVR, NDPC occurred at (13,1 ± 3,4)% of surveyed: equally common were : astheno-hypochondriac variant - (3,0 ± 1,7)%, hypochondriac - ( 2,0 ± 1,4)% and senesto - hypochondriac - (1,0 ± 1,0)%, while hypothymic variant of NDPC detected significantly more - in (7,1 ± 2,6)). Among patients with a medium CVR it was found that the frequency of NDPC in this group was significantly (p ≤ 0,05) higher (28,4 ± 4,5)%, and, in the structure of NDPC groups with an medium CVR significantly hypochondriac and hypothymic clinical variants (respectively (9,8 ± 2,9)% and (11,8 ± 3,2)%) (p ≤ 0, 05) were dominated, while the astheno - and senesto - hypochondriac variants registered at the level of 2-4%. Among patients with high CVR it was found, that NDPC occurred significantly (p ≤ 0,05) more often, than in patients with CVD (respectively (18,6 ± 3,9)% and (2,0 ± 1,4)%), and, in the structure of NDPC groups with high CVR, astheno - hypochondriac and hypothymic clinical variants of NDPC was prevailed. Thus, a hypothymic clinical variant of NDPC is the most common among groups of patients, while hypochondriac - registered significantly more often in patients with medium CVR, and astheno - hypochondriac - in patients with high CVR. Given is evidence in favor for the development of differentiated activities and individualized approach to medical and psychological monitoring system and clinical psychological support for people with high levels of CVR.